Will novel coronavirus (Covid-19) pandemic impact agriculture, food security and animal sectors? (Bioscience Journal, 2020)
The whole world is in a great danger due to the novel coronavirus (COVID-19) pandemic. In December 2019, the outbreak of COVID-19 took place in Wuhan, China and then rapidly spread all over the world. The current study provides potential expectations for the adverse impact of (COVID-19). The global infection affected globe on agricultural level such as agriculture, food supplies and animal production sectors. Till today, 29th April 2020, there is no vaccine available for treating novel coronavirus, consequently, the outbreak resulted in closing borders and reducing production following social distancing measures. This short communication illustrates the possible implications and expected outcomes of the outbreak of coronavirus (COVID-19) on agricultural, food security, integrated pest management (IPM), animal productivity; and it predicts, as well, the possible adverse impacts on the economy worldwide. Brazil has one of the most important tropical agriculture in the world, being a leader in soybean production in the world. This chain impacts others such as meat and eggs. The impact of COVID-19 will be positive, encouraging the country to consolidate its leadership in the world market, stimulating exports, the machinery, inputs and fertilizers market, as well as generating employment and income in the country.